THE ROLE OF SPORTS MANAGEMENT IN IMPROVING THE PERFORMANCE OF SPORTS TEAMS: A SYSTEMATIC REVIEW - Saleh Ali dnhash; Oras Qassim Mohammed; Sufyan Abdel Latif Mahmoud; Ali Yahya Abdulrzaq; Anas Diaa Khader (Proximus Journal Publishing, 2025)
This study focuses on sports management’s impact on sports teams’ performance. As a research domain, sports management is a very broad concept covering an extensive and diverse range of different disciplines, fields, and activities designed to improve both individual and team performance, image, behavior, and other relevant aspects of professional or amateur sports. It plays a pivotal role in creating ideal conditions that help teams to deliver on the field. On the one hand, this is done through a broad spectrum of management activities such as planning, organization, coordinating, directing, and controlling given resources. Sports management builds the foundation on which functional, desirable, competent, and successful organizational structure operates. Sports management also actively looks to improve the environment in which a sports team competes. An appropriate competitive environment puts the focus on the actual play and players, making the outcomes fair but unpredictable. And creates a stage in which attention is shifted from politics, bribery, or other unwanted conditions. On the other hand, adequate training of sports and coaching personnel, a talented sports team, time, dedication, and certain strategic moves that may work with a bit of luck are needed for a sports team to succeed. Proper coaching involves also effective communication, instruction, and an overall controlled behavior of managers and coaches before, during, and after a game, as they deal directly with sports team members, club owners, media, and fans. Moreover, disciplinary problems among players, opposing team members, and club managers are a widespread issue in sports, and their eventual management is crucial to avoid owners from losing money, stars not becoming addicted, or teenagers not getting involved in gambling addictions. A dispute often occurs between sports team members, owners, managers, and coaches, over money, playtime, bonuses, or other business-related activities. Expensive lawsuits, fines, or even penalties on points in championships can be the main consequences, ultimately causing the reputational image of the sports team to get tarnished. Additionally, at a higher level of sports, the behavior of a sport's team members off the field may end in firing, no tender offers, or sport suspension
Keywords: sports management; elite teams; artificial intelligence